COMPARISON OF THE REASON FOR WRITING THE WORK IN THE MANUSCRIPTS OF "TAZKIRAI SHUARO" - Dustova Surayyo Savronovna (International Engineering Journal For Research & Development, 2020)
This article provides information about the manuscripts of Tazkirai Shuaro. The similarities and differences in the reason for writing the work in the manuscripts of the tazkira are also studied and conclusions are drawn..